Phylogeny of Marine Ornamental Fish Members of Labridae from the South Coast of West Java, Indonesia - Pambudi, Dion Satrio; Nuryanto, Agus; Prabowo, Romanus Edy (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2019)
Labridae is a large and diverse fish family. Many species under Labridae inhabits Indonesian coral reefs. However, limited scientific data are available on ornamental fish diversity in Labridae from the South Coast of West Java. The purpose of the research is to give information about species diversity and phylogenetic relationships among species of Labridae fish family in the South Coast of West Java. This research will be conducted using a survey method with a purposive sampling technique. The observed parameters include morphometric and meristic characters and evolutionary relationships among species within Labridae family species collected from the South Coast of Sukabumi and Garut, West Java. Morphological data will be analyzed descriptively based on morphometric and meristic data. Species-level identification performed by referring to the available identification guide book. Phylogenetic relationships will be analyzed statistically using cladistics method as implemented in PAUP 4.0 applying maximum parsimony algorithm. The cladogram has a consistency index of 0.563, indicating low homoplasy and proved that the tree was the most parsimonious. Labridae formed monophyletic clade compared to Acanthurus maculiceps, and Cheilio inermis was basal species while the others derived species.